2012
DOI: 10.2516/ogst/2012020
|View full text |Cite
|
Sign up to set email alerts
|

Energy Equation Derivation of the Oil-Gas Flow in Pipelines

Abstract: Résumé -Dérivation de l'équation d'énergie de l'écoulement huile-gaz dans des pipelines -Lors de la simulation d'un écoulement multiphasique huile-gaz dans une conduite, le calcul thermodynamique représente un processus important en interaction avec le calcul hydraulique ; il influence la convergence du programme et la précision des résultats. La forme de l'équation d'énergie constitue la clef du calcul thermodynamique. Basée sur l'équation d'énergie de l'écoulement huile-gaz dans un pipeline, la formule de ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…The continuity equation and momentum equation are also called hydraulic equations, and the energy equation is also called the thermodynamic equation. These equations can be written in a general form (Sanaye and Mahmoudimehr, 2012;Zheng et al, 2012;Duan et al, 2013;Wang et al, 2015Wang et al, , 2018, as shown in Equation 1, and the parameters of the general form are given in Table 1.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The continuity equation and momentum equation are also called hydraulic equations, and the energy equation is also called the thermodynamic equation. These equations can be written in a general form (Sanaye and Mahmoudimehr, 2012;Zheng et al, 2012;Duan et al, 2013;Wang et al, 2015Wang et al, , 2018, as shown in Equation 1, and the parameters of the general form are given in Table 1.…”
Section: Governing Equationsmentioning
confidence: 99%
“…According to the operating conditions (pressure, temperature, liquid and gas superficial velocities, pipe orientation, and fluid properties) [2], both phases will be distributed in a certain topology called flow pattern. The knowledge of the latter is required for a better estimation of the hydrodynamics, thermal properties [3], choice of models closures in transient multiphase flow simulation codes [4,5], as well as for the modeling of flow assurance phenomena such as wax deposition [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is shown by Ahmed [3] that at temperature around 288, 15°k, wax will start to form inside the pipeline and at temperature below 313, 15°k, combine with high-pressure gas hydrates will occur. As results of these issues, pipe effective flow area may reduce and if serious, blockage may occur [4]. In subsea area, the interaction between the cold surrounding water and the warm flowing fluids inside pipeline is a major cause of temperature drop, which is responsible of some flow assurance issues such as wax deposition, and risk of hydrates formation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the work done by Zulkefli and Pao [5], this paper focuses on choosing and sizing of an insulation material to meet an output temperature of an oil and gas transporting pipelines in a subsea area from a wellhead to a surface processing plant. The particular points of this work that differ from [4] are:…”
Section: Introductionmentioning
confidence: 99%